1996
DOI: 10.1021/jm950410b
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Arylpiperazines, (Aryloxy)propanolamines, and Tetrahydropyridylindoles to the 5-HT1A Receptor:  Contribution of the Molecular Lipophilicity Potential to Three-Dimensional Quantitative Structure−Affinity Relationship Models

Abstract: A set of 280 5-HT1A receptor ligands were selected from available literature data according to predefined criteria and subjected to three-dimensional quantitative structure-affinity relationship analysis using comparative molecular field analysis. No model was obtained for serotonin analogues (19 compounds) and aminotetralins (60 compounds), despite a variety of alignment hypotheses being tried. In contrast, the steric, electrostatic, and lipophilicity fields alone and in combination yielded informative models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
5
31
0
4
Order By: Relevance
“…These alternative solutions might correspond to alternative binding modes which can ideally be supported by complementary model building studies of ligand-receptor complexes. A recent CoMFA analysis of the 5-HT 1A ligands documents such a situation [54]. The study revealed a single mode of interaction for arylpiperazines, aryloxypropanolamines and tetrahydropyrindoles at the 5-HT 1A receptor, whereas for serotonin and aminotetralines no single dominant binding model could be derived, which is indicative of the existence of alternative binding modes andyor of the inherent information poverty of the available data set [54].…”
Section: Mutagenesis Data Based Models Of the 5-ht 1a Receptor Locatementioning
confidence: 91%
See 1 more Smart Citation
“…These alternative solutions might correspond to alternative binding modes which can ideally be supported by complementary model building studies of ligand-receptor complexes. A recent CoMFA analysis of the 5-HT 1A ligands documents such a situation [54]. The study revealed a single mode of interaction for arylpiperazines, aryloxypropanolamines and tetrahydropyrindoles at the 5-HT 1A receptor, whereas for serotonin and aminotetralines no single dominant binding model could be derived, which is indicative of the existence of alternative binding modes andyor of the inherent information poverty of the available data set [54].…”
Section: Mutagenesis Data Based Models Of the 5-ht 1a Receptor Locatementioning
confidence: 91%
“…A recent CoMFA analysis of the 5-HT 1A ligands documents such a situation [54]. The study revealed a single mode of interaction for arylpiperazines, aryloxypropanolamines and tetrahydropyrindoles at the 5-HT 1A receptor, whereas for serotonin and aminotetralines no single dominant binding model could be derived, which is indicative of the existence of alternative binding modes andyor of the inherent information poverty of the available data set [54]. The strikingly different results which are obtained for the superposition of three``double'' monoamine ligands corresponding to the three possible heterogeneous combinations of the constituting ligand fragments by either accepting à`t wo site'' or a``three site'' hypothesis are indicative of the dilemma of structural alignments for monoamine ligands.…”
Section: Mutagenesis Data Based Models Of the 5-ht 1a Receptor Locatementioning
confidence: 99%
“…Gaillard et al [63] an electron-rich region (Ser-199) close to nitrogen of the indole ring of tetrahydropyridylindoles. The receptor model also indicated that a large region was allowed for the nitrogen substituent between helices III, VI and VII.…”
Section: Serotonin Receptor ( Receptor)mentioning
confidence: 99%
“…The most significant application of these maps, however, is that they can be imported into 3D QSAR programs such as CoMFA [32] as hydropathic/hydrophobic fields to supplement the standard complement of steric and electrostatic field types. Since we first reported the HINT/CoMFA interface numerous studies have been performed using HINT [33][34][35][36][37][38] as well as other lipophilic field models [39,40] with 3D QSAR. Our experience is mixed.…”
Section: Hint 3d Property Maps (Including 3d Qsar)mentioning
confidence: 99%